Solve the equation 2log (base 3)(x) - log (base 3)(x+4) = 2


First express as a single logarithm as follows. The number in front of the logarithm remembering log rules can be rewritten as the power of the number in the bracketsSo rewriting the RHSlog3(x2) - log3(x+4)log3(x2/(x+4))remember inverse log3 is to the power of 3so2 = log3(x2/(x+4))32=(x2/(x+4))expanding and solving x2-9x-36=0(x-12)(x+3)=0x=12 as cannot do a negative logarithm of a number

Looking for more help? Search our library of answers.👇

Need help with Maths?
Boost your grades with stress-free tuition that fits your schedule.

About the author

Theranjit S. is an online Maths tutor with MyTutor studying at Imperial College London University